2022
DOI: 10.3390/w14244049
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Metal Ions from Wastewater by a Greener Approach

Abstract: The examination of the performance of raw and immobilized S. (Saccharomyces) cerevisiae in the simultaneous abatement of metal ions from wastewater effluent is the focal point of this article. The optimal storage time for raw and immobilized S. cerevisiae, during which they can be utilized, was estimated. The outcomes revealed that as the initial metal ion concentrations increased, the adsorption capacity improved, while the removal efficiency of S. cerevisiae yeast cells decreased, with the highest uptake obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In the spectra of metal-loaded biomass, there has been no formation of new bands, indicating that the biosorption of studied metal ions process occurs mainly through ion-exchange interaction that is electrostatic [ 21 , 43 ]. Thus, in the spectrum of yeast biomass after silver ion biosorption, the shift of the bands corresponding to OH, CH=CH, –NH, and sulfo groups by 5–15 cm −1 was observed indicating their involvement in silver ion binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spectra of metal-loaded biomass, there has been no formation of new bands, indicating that the biosorption of studied metal ions process occurs mainly through ion-exchange interaction that is electrostatic [ 21 , 43 ]. Thus, in the spectrum of yeast biomass after silver ion biosorption, the shift of the bands corresponding to OH, CH=CH, –NH, and sulfo groups by 5–15 cm −1 was observed indicating their involvement in silver ion binding.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with Staron et al [ 10 ] and Zhao et al [ 34 ], who used coconut fiber and graphene oxide for silver sorption. Applicability of the pseudo-second model suggests that metal ion binding on the surface of S. cerevisiae is achieved via chemical interactions that include two active centers in favorable geometric positions [ 43 ]. It is suggested that the adsorption of the investigated metal ions occurs mainly due to ion exchange and surface complexation reactions at specific biosorption sites [ 34 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…MT3 biosorbent has a higher desorption capacity and is used in more cycles than various biosorbents where a lower Pb concentration was applied (Gong et al, 2005, Kumari et al, 2017, Huang & Liu, 2013). Ibrahim et al (2022) reported that immobilized S. cerevisiae desorbed 100‐mg L −1 Pb by approximately 45%. These studies support our findings.…”
Section: Resultsmentioning
confidence: 99%
“…A green approach to wastewater treatment is explored in the paper: Simultaneous Removal of Metal Ions from Wastewater by a Greener Approach [48]. The research emphasizes the significance of sustainable and environmentally friendly methods for metal ion removal from contaminated water sources.…”
Section: Materials Methods and Resultsmentioning
confidence: 99%